Can our phones keep us safe? A content analysis of smartphone applications to prevent mobile phone distracted driving. (January 2019) - Oviedo-Trespalacios, Oscar; King, Mark; Vaezipour, Atiyeh; Truelove, Verity
Graphical abstract: Highlights: 29 smartphone applications which prevent distracted driving were identified. These applications focus on blocking phone functions. Ecosystem of smartphone applications was used to examine their functionality. The applications do not focus on simplifying phone tasks while driving. Abstract: Mobile phone use while driving is a pervasive problem that continues to increase, notwithstanding the large crash risk this behaviour constitutes. A number of phone applications have been developed with the intention of utilising the technology to prevent dangerous phone behaviours while driving. Despite the potential these applications have in preventing crashes associated with distracted driving, research is yet to explore these emergent applications. Therefore, this study provided a review of the current smartphone applications developed to prevent distracted driving. A content analysis was conducted to identify the smartphone applications targeted at stopping, preventing or reducing phone use behaviour while driving. Their functionality was determined based on the ecosystem of smartphone applications: application-mobile phone interaction, application-driver interaction, and application-context interaction. A total of 29 relevant applications in English language were identified. Most of these applications focused on blocking specific phone functions (e.g. texting or calling) while allowing more desirable driving phone functions to be accessed (e.g. music applications and GPS functions). The specific functions which are blocked or allowed varied greatly between applications. Out of the different application interactions, the function which sends an automatic text message to a contact who texts the driver (associated with external communicator interactions) was the most common feature. A major limitation of the applications was their reliance on blocking specific phone functions as opposed to managing workload while driving or simplifying specific phone tasks to be more compatible with driving. Simply blocking phone functions may not be attractive to drivers who view their phone as a necessity. As such, these drivers are unlikely to use these voluntary applications at all while driving. Smartphone applications designed to prevent phone use while driving show potential for playing a large role in a systemic intervention to prevent mobile phone distracted driving, yet there is a substantial need for further development of these applications.